The effect of chitosan levels in feed on the growth and daily feed consumption of giant gourami (Osphronemus goramy) - Dito Maryanto Putra; Roffi Grandiosa; Herman Hamdani; Kiki Haetami (Depik, 2021)
Chitosan is an ingredient that can be used as a feed additive. In aquaculture, chitosan can be used as an antimicrobial, antifungal, antioxidant growth-promoting and immunostimulant. This study aims to determine the optimum addition of chitosan to feed to increase growth and daily feed consumption of giant gourami. The method used in this research is an experimental method using a completely randomized design (CRD), which consists of five treatments and three replications. The treatments used were (A) without chitosan (control), (B) 2.5 g/kg feed, (C) 5 g/kg feed, (D) 7.5 g/kg feed, and (E) giving chitosan of 10 g/kg feed. The test fish used were giant gourami with a 6 – 8 cm length and a weight of 8 – 10 g. The container used was hapa measuring 1 x 1 x 1 m3 with a density of 15 fish per treatment and 42 days of maintenance. The feeding rate was 3% of the fish biomass. Data from observations of length and weight were analyzed using Analysis of Variance (ANOVA) with a 95% confidence level; if there was a significant difference, Duncan's multiple distance test was performed. The results showed that addition of chitosan 7.5 g/kg feed was effective in improving growth on giant gourami. During maintenance, absolute length growth was 2.90 ± 0.10 cm, absolute weight growth was 15.33 ± 1.19 g, daily growth was 36.51 ± 2.84%, feed conversion ratio was 1.69 ± 0.06, and survival rate was 100 ± 0.00%. This research concluded that the optimum level of addition of chitosan to increase growth and daily feed consumption of giant gourami was 7.5 g/kg feed.Keywords:ChitosanFeed additiveGiant gouramiGrowth